Amplitude analysis of B+ → ψ(2S)K+π+π− decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Journal of high energy physics, 2025)
The first full amplitude analysis of B+ → ψ(2S)K+π+π− decays is performed using proton-proton collision data corresponding to an integrated luminosity of 9 fb−1 recorded with the LHCb detector. The rich K+π+π− spectrum is studied and the branching fractions of the resonant substructure associated with the prominent K1(1270)+ contribution are measured. The data cannot be described by conventional strange and charmonium resonances only. An amplitude model with 53 components is developed comprising 11 hidden-charm exotic hadrons. New production mechanisms for charged charmonium-like states are observed. Significant resonant activity with spin-parity JP = 1+ in the ψ(2S)π+ system is confirmed and a multi-pole structure is demonstrated. The spectral decomposition of the ψ(2S)π+π− invariant-mass structure, dominated by X0 → ψ(2S)ρ(770)0 decays, broadly resembles the J/ψϕ spectrum observed in B+ → J/ψϕK+ decays. Exotic ψ(2S)K+π− resonances are observed for the first time.
Im Titel sind die Zeichen "+" und "-" hochgestellt
Gesehen am 07.10.2025
The LHCb collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, S. Celani, C.E. Cocha Toapaxi, M. De Cian, L. Dittmann, S. Esen, F. Glaser, P.A. Günther, X. Han, S. Hausmann-Menzemer, P. Herrero Gascon, J. Hu, J. Kubat, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, P.R. Pais, S.R. Roy, M. Ruiz Diaz, M. Schmelling, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov und weitere 1084